2021
DOI: 10.1093/ptj/pzab273
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Reinjury Following Surgical and Nonsurgical Management of Anterior Cruciate Ligament Injury: An Exploratory Analysis of the NACOX Multicenter Longitudinal Cohort Study

Abstract: Objectives The purpose of this study was to compare fear and certainty of reinjury between follow-up time points and treatment groups (no anterior cruciate ligament [ACL] reconstruction [no ACLR], pre-ACLR, post-ACLR) and to identify prognostic factors for fear of reinjury at 3 and 12 months following injury or ACLR. Methods An exploratory analysis of the NACOX multicenter longitudinal cohort study was conducted. Patients (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 66 publications
2
13
0
1
Order By: Relevance
“…Patients in earlier postoperative phases demonstrated greater kinesiophobia compared to patients in later recovery phases. One study reported decreases in kinesiophobia in their cohort of patients between the 3-and 12-month follow-up assessments following ACLR [17]. Results in this present review were consistent with their indings demonstrating that the degree of kinesiophobia was highest during the irst month (25.5 days) of rehabilitation and decreased signiicantly by the 7-month (224.9 days) mark.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Patients in earlier postoperative phases demonstrated greater kinesiophobia compared to patients in later recovery phases. One study reported decreases in kinesiophobia in their cohort of patients between the 3-and 12-month follow-up assessments following ACLR [17]. Results in this present review were consistent with their indings demonstrating that the degree of kinesiophobia was highest during the irst month (25.5 days) of rehabilitation and decreased signiicantly by the 7-month (224.9 days) mark.…”
Section: Discussionsupporting
confidence: 89%
“…It has been reported that men display greater self-eicacy and women tend to display greater anxiety towards rehabilitation and resuming activity following ACLR, and the degree of self-eicacy impacts kinesiophobia according to our results [44]. Additionally, women have been reported to show higher pain sensitivity, lower pain thresholds and greater fear and disability due to pain [17]. Further, patients with knee OA tend to have greater kinesiophobia following ACLR.…”
Section: Discussionsupporting
confidence: 58%
“…9 ACL injury is most common in adolescents and may have negative long-term physical and psychological effects. [9][10][11][12][13] The treatment is intended to restore knee function, overcome psychological barriers against participation in activities, 13 prevent further injury and osteoarthritis, and optimize the long-term quality of life. Current treatment options for ACL injury mainly include surgery and conservative treatment, with ACL reconstruction (ACL-R) surgery being generally adopted for patients who have high requirements for motor function.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] Studies have shown that ACL-R helps inhibit tibial anterior translation, restore normal knee biomechanics, restore knee stability, prevent excessive torsion, relieve pain, restore function, return to sports activity, and reduce the incidence of complications. 5,13,[21][22][23][24] Given that the success rate of ACL-R is related to graft dimensions, [25][26][27] it is necessary to have an accurate assessment of the dimensions of the ACL-R graft preoperatively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation